Abolition or mitigation of the death penalty - A perspective on the laws of Israel - F. N. Lion-Cachet (In die Skriflig, 1994)
The issue concerning the topic of the death penalty for capital offences is still widely discussed. Those supporting the retention of the death penalty mostly quote the Old Testament as their source of authority. The question, however, is whether confirmation has not been found too easily in the Old Testament, without fully taking into account the conditions of the period. Or should the death penalty not be applied for transgressions other than manslaughter as well? In this paper special attention will he given to the demand for the death penalty for manslaughter and other crimes. The question whether the implementation of the death penalty in the history of old Israel implies the retention or mitigation thereof, will also have to be answered.